Analysis of the Character Values of Gotong Royong in the Novel Bulan by Tere Liye and The Relevance to Literature Learning in Junior High School - Latifatun Na'mah (KREDO : Jurnal Ilmiah Bahasa dan Sastra, 2025)
The rapid era of globalization is one of the factors causing the fading of moral values and character of children in Indonesia. This study aims to describe the value of mutual cooperation in Tere Liye's novel Bulan and its relevance as a literary learning tool. This type of research is descriptive qualitative. The research data is in the form of quotations of words, phrases, clauses and sentences that contain the character values of mutual cooperation. The novel Bulan by Tere Liye is the source of data for this research. The data was obtained using reading, note-taking, and documentation techniques. Validation techniques used data source triangulation and semantic validity techniques. Data analysis used content analysis and dialectical analysis techniques. The results of this study show that the novel Bulan contains four components of mutual cooperation consisting of the values of mutual cooperation and cooperation, the values of tolerance and cross-cultural collaboration, the values of social responsibility, and the values of solidarity and friendship. The novel Bulan is relevant to the Learning Outcomes (CP) in the Indonesian Language subject content in grade IX of Junior High School.